Phenotypic and Functional Study of Human Plasmacytoid Dendritic Cells. Issue 4 (5th April 2021) - Li, Guangming; Cheng, Liang; Su, Lishan
Abstract: Plasmacytoid dendritic cells (pDCs) are a distinct lineage of bone‐marrow‐derived cells that reside mainly in blood and lymphoid organs in the steady state but are also present in sites of infection, inflammation, and cancer. The protocols in this article describes (1) detection and quantification of human pDCs in peripheral blood; (2) isolation of human pDCs by magnetic‐activated cell sorting (MACS) and fluorescence‐activated cell sorting (FACS); (3) evaluation of human pDC function by stimulation with TLR7 or TLR9 agonists; (4) detection of human pDCs in lymphoid tissues of humanized mice (hu‐mice) by flow cytometry; (5) functional study of human pDC in hu‐mice in vivo; and (6) specific depletion of human pDCs in vivo in hu‐mice using monoclonal antibody targeting human pDCs. These assays thus provide comprehensive methods for phenotypic and functional studies in vitro and for the investigation of human plasmacytoid dendritic cells in hu‐mice in vivo. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Analysis of pDCs in human peripheral blood mononuclear cells Basic Protocol 2 : pDC separation using MACS beads Alternate Protocol 1 : pDC sorting using flow cytometer Basic Protocol 3 : Evaluation of human pDC function by stimulation with TLR agonists in vitro Alternate Protocol 2 : Intracellular staining of cytokines in pDCs Basic Protocol 4 : Phenotypic analysis of human pDCs from lymphoid organs in humanized mice Basic Protocol 5 : Functional study of human pDCs in humanized mice during HIV infection Basic Protocol 6 : pDC depletion and assessment of pDC depletion in acute HIV‐infected in humanized mice